Man trouble - Rafelson, Bob 1933-; Gilbert, Bruce 1946-; Eastman, Carole 1934-2004; Eastman, Carole 1934-2004 (20th Century Fox Home Entertainment, 1992)
In this wild, romantic comedy with a decidedly offbeat sense of humor, Harry, a wise cracking con-man who owns a guard dog agency. When Joan, an opera singer, seeks his aid after her house is broken into, Harry inadvertently makes them the target of hit men - and puts them at eh mercy of Harry's out-of-control canines.